Do Audit Opinion, Audit Independence and Audit Quality Influence Whistle Blowing Policy? Evidence from Nigerian Exchange Group - Hussaini Bala; Anas Abdulwahab; Idris Adamu Adamu (STIM LASHARAN JAYA MAKASSAR, 2023)
Recent high-profile company cases around the world have heightened interest in how external auditors may improve whistleblower policies. However, the audit committee, board of directors, CEO, and ownership structure have been the main focus of the majority of the studies about reducing earnings management. Since this shift has occurred, the goal of this research is to examine how external auditors can improve whistleblower policy. The study used a correlational research design to evaluate data from 41 listed financial institutions in Nigeria for a period of 13 years (2009-2021), both years inclusive, in order to look into the relationship between the characteristics of the external auditors and whistle blowing policy. The outcome of the logistic regression analysis showed that the auditors' viewpoint, independence, and quality looked to be favorably connected with the whistle blowing policy. This study examines how the characteristics of external auditors influenced the whistleblowing policy procedure. Investors, regulators, and analysts should be interested in this paper's findings on the long-term strategic consequences of whistle blowing policies. As with most empirical studies, the model, methodology, variables, time frame, and companies studied in the paper all serve as restrictions. Other industries could be added to the sector, and additional auditor characteristics that were not covered in this study could be discovered through future research.